INTEGRITAS KEILMUAN DAN IMPLIKASI ETIS PENGGUNAAN ARTIFICIAL INTELLIGENCE DALAM PENELITIAN: A SYSTEMATIC LITERATURE REVIEW - Ainur Rofiqi; Fauziyah; Slamet Arifin; Siti Mas'ula (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of artificial intelligence (AI) in the scientific research ecosystem has accelerated significantly and offers efficiency at various stages of research, from data processing, analysis, to manuscript preparation. However, the use of AI raises new ethical challenges that have not been fully accommodated in conventional scientific integrity guidelines. This study is a Systematic Literature Review that aims to map research trends, integrity and ethical implications of the use of AI, as well as ethical challenges in the use of AI in scientific research and publications. The study was conducted on 25 scientific articles. The results of the study show an increasing trend, especially in 2019-2023. The use of AI is inseparable from ethical responsibility, academic transparency, and compliance with scientific publication guidelines. The challenges in the application of AI ethics are multidimensional, ranging from AI bias and ethical norms in scientific research, violations of AI in research, confidentiality and privacy, and morality in the use of AI. Therefore, an approach that combines normative ethical frameworks, technical operational standards, and adaptive and sustainable institutional governance is needed.